PENGELOLAAN KEUANGAN DAN DAMPAKNYA TERHADAP KEBERLANJUTAN USAHA MIKRO, KECIL, DAN MENENGAH DI KABUPATEN SEMARANG (Studi Kasus pada Toko Wahana Parfum Karangjati) - Zai, Miryam Menila; Widagdo, Chrisostomus Susmono (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to examine the complexities of financial management and their impact on the survival of micro, small, and medium-sized enterprises (UMKM) in Semarang district, with special emphasis on Wahana Parfum Shop in Karangjati. Although UMKM continues to flourish in Semarang district, many are facing obstacles in managing their finances effectively, as only a small fraction are active and skilled to manage their financial affairs. Conversations with business owners have found that the main challenge lies in their lack of understanding of the benefits of financial statements and incomplete financial controls. Besides, perfume entrepreneurs show a lack of confidence when comparing financial plans to real life circumstances. It underscores the need to overcome gaps in financial literacy and financial management to improve the performance and resilience of SMEs in the region. Recommendations include offering training and education to enhance understanding of financial management, maximize the use of business control, and cultivate a deeper understanding of the principles of finance management.